Parental Perception of Self-Empowerment in Pediatric Pharmacogenetic Testing: The Reactions of Parents to the Communication of Actual and Hypothetical CYP2D6 Test Results. Issue 9 (2nd September 2017) - Adelsperger, Sarah; Prows, Cynthia A.; Myers, Melanie F.; Perry, Cassandra L.; Chandler, Ariel; Holm, Ingrid A.; Lynch, John A.
ABSTRACT: Concerns about the ethical and social implications of genetics persist as more applications of genetic and genomic technology have become available. Pediatric testing for genetic influences on response to opioids like codeine is one area of application. We interviewed parents of children enrolled in a mixed-methods study following the communication of actual or hypothetical results for CYP2D6, which impacts opioid response. Forty-one parents of children naive to opioids and 42 parents of children previously exposed to opioids participated in qualitative interviews. Findings did not differ by the child's opioid exposure or by actual versus hypothetical results. Parents' responses centered on the experience of the parent(s) and the potential impact of that information on the parent, rather than the result's impact on the child. Parents also emphasized that the results did not impact their perceptions of the child, reaffirming that the child was still "normal" regardless of test result. When asked about the impact of receiving secondary results, parents' responses emphasized how the results would impact their ability to advocate for the child or impact their state of mind. While the answers reflect parents' role as surrogate decision maker for their child, they also reinforced concerns that health care decisions might be influenced by secondary parental concerns as much as by the best interests of the child. Emphasis on the child's "normality" challenges concerns about the impact of genetic essentialism, but further research is required to see whether the type of testing done or the way results were communicated shaped this response.